The Relationship Between Forgiveness and Subjective Well-Being Among Adolescents Living in Orphanages - Salsabila Febrina Putri; Santi Esterlita Purnamasari (SEAN Institute, 2026)
This study aims to examine the relationship between forgiveness and subjective well-being among adolescents residing in orphanages. It posits the hypothesis of a positive relationship between forgiveness and subjective well-being in this population. The participants comprised 110 adolescents aged 13–18 years. Data were collected using the Satisfaction with Life Scale (SWLS), Scale of Positive and Negative Experience (SPANE), and Transgression-Related Interpersonal Motivations Inventory-18 (TRIM-18). Product-moment correlation was employed for data analysis. Results revealed a correlation coefficient (rxy) of 0.827 with p = 0.000 (p < 0.001), supporting the hypothesis of a positive correlation. The coefficient of determination (R2) was 0.683, indicating that forgiveness accounts for 68.3% of the variance in subjective well-being, with the remaining 31.7% attributable to other factors.